Pelatihan Penulisan Artikel Ilmiah untuk Guru - Sri Jumini; Mila Ariyani; H Hamzah; H Hidayat; Heri Priyanto (Jurnal Pemberdayaan Masyarakat, 2024)
The scientific article writing training program implemented at SMA N 1 Wadaslintang aims to improve the skills of teachers and students in writing quality scientific articles. This program is designed to equip teachers and students with technical skills in scientific writing as well as develop systematic research abilities. This research uses a Participatory Action Research (PAR) approach, which places teachers and students as active participants in every stage of the program, from planning, and implementation, to evaluation. With this approach, teachers and students are not only the objects of training but also participate in the process of reflection and improvement of the program. Through the PAR approach, it is hoped that students can understand more deeply the scientific writing process and make a direct contribution to improving the quality of learning. The results of this training show a positive impact on scientific article writing skills. This is proven by the participants who got a perfect score of 100 on the competency test. They can write more structured and follow correct scientific principles. This program also succeeded in increasing motivation to continue developing writing and research skills.